REDESAIN HALTE TRANS JATENG DENGAN PRINSIP ERGONOMIS DAN BERKESALAMATAN DI KABUPATEN MAGELANG (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
The construction of bus stops is often neglected because it does not provide a sense of security and comfort, especially for people with disabilities. The purpose of this study was to analyze and redesign the Balikondes Kembang Limus bus stop in Magelang Regency. The research methodology used is a qualitative method which is described descriptively through an anthropometric approach and design science, field observations and observations regarding the condition of the shelter design will be studied. This redesign takes into account functional aspects, ergonomic aspects, visual aspects, and safety aspects. The function aspect explains the suitability of the function of the bus stop itself and the bus stop facilities, for example seating facilities as passenger seats. The ergonomic aspect explains the suitability of the redesign with the dimensions of the human body in order to provide comfort in moving and provide a sense of security which includes redesign of the chair and ramp. The visual aspect explains the visual form of the bus stop to make it attractive. As well as the safety aspect, it explains the addition of safety facilities which include CCTV, fire extinguisher, waiting room, ramp for the disabled, raumble strip, handrail, and installation of building blocks. ABSTRAK Pembangunan halte bus sering terabaikan karena tidak memberikan rasa aman dan nyaman, khususnya bagi penyandang disabilitas. Tujuan dari penelitian ini untuk menganalisis dan redesain Halte Balikondes Kembang Limus di Kabupaten Magelang. Metodologi penelitian yang digunakan yaitu dengan metode kualitatif yang dipaparkan secara deskriptif melalui pendekatan anthropometri dan ilmu desain, dilakukan pengamatan lapangan dan observasi mengenai kondisi rancangan halte yang akan dikaji. Perancangan redesain ini mempertimbangkan aspek fungsi, aspek ergonomis, aspek rupa, dan aspek keselamatan. Aspek fungsi menjelaskan kesesuaian fungsi dari halte itu sendiri dan fasilitas halte misal fasilitas tempat duduk sebagai tempat duduk penumpang. Aspek ergonomis menjelaskan kesesuaian redesain dengan dimensi tubuh manusia agar memberikan kenyaman dalam bergerak dan memberikan rasa aman yang meliputi redesain pada kursi dan ramp. Aspek rupa menjelaskan bentuk visual halte agar menarik. Serta aspek keselamatan menjelaskan penambahan fasilitas berkeselamatan yang meliputi CCTV, APAR, ruang tunggu, ramp untuk disabilitas, raumble strip, handrail, dan pemasangan guiding block.